2015
DOI: 10.1007/s11356-015-4762-6
|View full text |Cite
|
Sign up to set email alerts
|

Indoor air quality in a restaurant kitchen using margarine for deep-frying

Abstract: Indoor air quality has a great impact on human health. Cooking, in particular frying, is one of the most important sources of indoor air pollution. Indoor air CO, CO 2 , particulate matter (PM), and volatile organic compound (VOC) concentrations, including aldehydes, were measured in the kitchen of a small establishment where a special deepfrying margarine was used. The objective was to assess occupational exposure concentrations for cooks of such restaurants. While individual VOC and PM 2.5 concentrations wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…In addition, the concentrations of suspended particulates and TVOCs were measured in official building as control levels. 21…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the concentrations of suspended particulates and TVOCs were measured in official building as control levels. 21…”
Section: Methodsmentioning
confidence: 99%
“…In three residence measurements conducted by Zhang et al (2010), it was also found that, during boiling, lower UFPs concentrations were observed, while the UFPs levels were higher during frying. Many researches have reported similar results (Rogge et al, 1991;Buonanno et al, 2010;Taner et al, 2013;Sofuoglu et al, 2015). A summary of the particle concentrations generated from different cooking methods are presented in Table 5.…”
Section: Cooking Methodsmentioning
confidence: 67%
“…Regarding cooking exposures, an analysis of NHANES data has shown that children whose parents report using ventilation while cooking with gas stoves are less likely to be diagnosed with asthma than children whose parents do not ventilate their gas stoves. {Kile:2014fd} Certain types of cooking, particularly frying, [ 15 ] are known to create large amounts of particulate matter. Thus, encouraging minimal use of frying could have respiratory benefit as well as dietary benefits for the household.…”
Section: Discussionmentioning
confidence: 99%
“…A recently published report of measured PM 2.5 in 13 residences in Seoul demonstrated differences depending on the type of ventilation used during a cooking task [ 13 ]. A few studies of cooking exposures in restaurants also have shown markedly elevated PM levels associated with particular types of cooking (especially frying)[ 14 , 15 ] and have even shown associations between airborne particles from cooking and inflammatory markers in exposed people[ 16 , 17 ]. In addition, recent work has demonstrated that some of the airborne particles produced from cooking can result from fuel combustion (gas) [ 18 ] as well as from organic material that is adsorbed to the cooking surfaces even in the absence of fuels which produce particles when combusted (such as electric stoves).…”
Section: Introductionmentioning
confidence: 99%